Mechanical Properties of Two Kinds of 2.5D Quartzf/Silica Composites by Silica Sol-Infiltration-Sintering - Liu, Yong; Zhu, Jianxun; Chen, Zhaofeng (Asian Journal of Chemistry, 2012)
Two kinds of 2.5D (shallow bend-joint and shallow straight-joint) quartz fiber-reinforced silica composites were prepared by silica sol-infiltration-sintering method. Mechanical properties of the composites and the structure characteristics of the 2.5D preforms were compared. The mechanical properties examined included tensile strength, flexural strength and shear strength. The results of the mechanical tests indicated that 2.5D (shallow bend-joint) quartzf/silica composite had a higher flexural strength and shear strength than 2.5D (shallow straight-joint) quartzf/silica composite. The tensile strength of 2.5D (shallow straight-joint) quartzf/silica composite were superior to that of 2.5D (shallow bend-joint) quartzf/silica composite.